Wearable Focal Muscle Vibration Device for Reducing Spasticity and Improving Upper Limb Function: Device Co-Design and Results From a Feasibility Study in People With Stroke - Moeez Ashfaque; Elizabeth Mills; Jamie Grant; Charlotte Vye; Alison Watt; Amy Dennis Jones; Simon F. Farmer; Amit N. Pujari (IEEE Journal of Translational Engineering in Health and Medicine)
Objective: This study set out to co-design a wearable Focal Muscle Vibration (FMV) device and test its feasibility as a rehabilitation tool to reduce spasticity and improve upper limb function in stroke population. Methods: The objective was achieved through carrying out: a) a semi-structured workshop involving chronic stroke patients, clinicians and researchers to gather systematic user feedback, b) changes to the device design based on this feedback, c) feasibility study comparing effectiveness of 40 minutes of INTERVENTION (FMV+ conventional therapy) with CONTROL (conventional therapy alone), in reducing spasticity and improving upper limb function in 10 stroke participants, d) Quantitative (Fugl Meyer Upper Limb (FMUL), Modified Ashworth (MASh), Pittsburgh Rehabilitation Participation Scale (PRPS), Recruitment Rate and Retention Rate)) and Qualitative (verbal and written feedback), measures to assess participants perception of the wearable technology and its potential as a rehabilitation tool in reducing spasticity and improving function. Results: Participant recruitment and retention rates were high (>80%) along with high PRPS score (6/6), indicating high level of participant engagement throughout the study. FMV intervention improved FMUE scores compared to the Control however did not improve MASh scores. Discussion/Conclusion: This study systematically investigated a wearable FMV device to reduce spasticity and/or improve upper limb function in stroke patients, from co-designing a device with patients and clinicians to carrying out a feasibility study. Clinical outcome measure indicates technology’s potential in improving upper limb function but reduction in spasticity was non-significant, potentially due to small population and duration of intervention. Participants feedback on usability the and acceptability of the technology was also highly positive, indicating its potential as a transformative rehabilitation tool. Clinical and Translational Impact—The Focal Muscle Vibration (FMV) device co-developed and tested in this study has significant potential as a wearable, easy to use, rehabilitation aid to improve upper-limb function in stroke patients.